Speeches for the Dead : Essays on Plato's Menexenus - Parker, Harold (Harold Graham); Robitzsch, Jan Maximilian (Beiträge zur Altertumskunde ;, 2018)
The Menexenus, in spite of the dearth of scholarly attention it has traditionally received compared to other Platonic texts, is an important dialogue for any consideration of Plato's views on political philosophy, history, and rhetoric - to say nothing of the dialogue's contribution to the study of civic ideology and institutions, natural law theory, and Plato's notion of race. Speeches for the Dead unites the contributions of scholars working on diverse aspects of the dialogue, growing out of a one-day workshop on the same subject at the University of Pennsylvania organized by the editors. In offering a variety of perspectives on the Menexenus, the volume is the very first of its kind in any language. In addition, the volume contains an up-to-date bibliography of scholarship in English, French, German, and Italian. This makes the book a definitive guide and ideal starting point for advanced students and scholars looking for further information about the dialogue.